2021
DOI: 10.1111/clr.13735
|View full text |Cite
|
Sign up to set email alerts
|

Immediate one‐piece zirconia implants with/without xenograft in the buccal gap: A 6‐month pre‐clinical study

Abstract: Objective To histologically evaluate healing following grafting a xenogenous bone substitute in the buccal gap around the immediately placed one‐piece zirconia implant. Materials and methods The third and fourth premolars (PM3 and PM4) in both quadrants of the mandible of nine Mongrel Hound dogs were used for this experiment. They have been removed, and the recipient sites were prepared. The implants were placed in a lingual position in the socket. In one side of the jaw, the gap between the implant and the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…This author had results contrary to those found by Araújo et al (2011) in dogs and Sanz et al (2017) in humans, that found that placing a demineralized bovine bone mineral with 10% collagen (DBBM-C) in the gap significantly reduced the horizontal bone resorptive changes occurring in the buccal bone after the immediate implantation in fresh extraction sockets. Regarding zirconia implants, it is known that the placement of DBBM-C in the gap between a 1-piece zirconia implant and the buccal wall in dogs modified the process of hard tissue healing providing an additional amount of hard tissue (Alves et al, 2021), that is, similar results to those found by Araújo et al (2011) and Sanz et al (2017) with titanium implants. Benic et al (2017) have concluded that zirconia and titanium implants grafted with DBBM granules and covered with a collagen membrane did not perform differently regarding the augmented ridge contour, the new bone formation and the implant osseointegration.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…This author had results contrary to those found by Araújo et al (2011) in dogs and Sanz et al (2017) in humans, that found that placing a demineralized bovine bone mineral with 10% collagen (DBBM-C) in the gap significantly reduced the horizontal bone resorptive changes occurring in the buccal bone after the immediate implantation in fresh extraction sockets. Regarding zirconia implants, it is known that the placement of DBBM-C in the gap between a 1-piece zirconia implant and the buccal wall in dogs modified the process of hard tissue healing providing an additional amount of hard tissue (Alves et al, 2021), that is, similar results to those found by Araújo et al (2011) and Sanz et al (2017) with titanium implants. Benic et al (2017) have concluded that zirconia and titanium implants grafted with DBBM granules and covered with a collagen membrane did not perform differently regarding the augmented ridge contour, the new bone formation and the implant osseointegration.…”
supporting
confidence: 58%
“…The present experiment demonstrated that the placement of xenograft with 10% collagen into the buccal gap between a one-piece zirconia implant and bone walls of a fresh socket of dogs modified the process of soft tissue healing, providing a more coronal position of the peri-implant mucosal margin. This publication is the continuation of the study of Alves et al (2021), and, therefore, the results are correlated.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…dimensionA mongrel dog study analyzed the effect of placing DBBM-C into the buccal gap in one piece zirconia implants 76. A total of 36 implants were immediately placed with flapless approach at a lingual position of mandibular premolars.…”
mentioning
confidence: 99%